2018
DOI: 10.1007/s12011-018-1260-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of In Ovo Zinc Injection on the Embryonic Development and Epigenetics-Related Indices of Zinc-Deprived Broiler Breeder Eggs

Abstract: The role of in ovo zinc (Zn) injection in improving the embryonic development in eggs from Zn-deficient hens, via epigenetic and antioxidant mechanisms, was examined. A completely randomized design involving a 1 (the non-injected control) + 1 (the injected control with sterilized water) + 2 (Zn source) × 2 (Zn level) factorial arrangement of treatments was used. The two injected Zn sources were inorganic Zn sulfate and organic Zn-lysine chelate with a moderate chelation strength, and the two injected Zn levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 26 publications
1
20
0
Order By: Relevance
“…Nanoparticles have been reported to be more efficient for animals than larger particles at low doses due to the easy absorption and biological availability as well as appear to interact better with other materials due to the significance of the active surface (Khalil et al, 2013;Wang et al, 2015;El Basuini et al, 2016, 2017. In the present study, hatchability percentage of Inshas strain was affected by in ovo zinc supplementations, which is in line with the previous studiesreported by Joshua et al(2016); Jose et al (2018); Sun et al (2018). Results indicate thatin ovo ZnO-NPs by up to 60 µg/ egg has no adverse effect onhatchability percentagebut decreases with increasingZnO-NPs above 60 µg per egg.…”
Section: Phagocytic Activitysupporting
confidence: 91%
See 2 more Smart Citations
“…Nanoparticles have been reported to be more efficient for animals than larger particles at low doses due to the easy absorption and biological availability as well as appear to interact better with other materials due to the significance of the active surface (Khalil et al, 2013;Wang et al, 2015;El Basuini et al, 2016, 2017. In the present study, hatchability percentage of Inshas strain was affected by in ovo zinc supplementations, which is in line with the previous studiesreported by Joshua et al(2016); Jose et al (2018); Sun et al (2018). Results indicate thatin ovo ZnO-NPs by up to 60 µg/ egg has no adverse effect onhatchability percentagebut decreases with increasingZnO-NPs above 60 µg per egg.…”
Section: Phagocytic Activitysupporting
confidence: 91%
“…The highest phagocytic activities were observed in D30C60, D30C80, and D30C100 groups. DISCUSSIONS Zinc at adequate level plays serious roles in the overall performance of animals including poultry, as it involves in an assortment of biological systems and is the main component of a large number of enzymes (Akbari et al, 2016(Akbari et al, , 2018Torres and Korver, 2018;Zhang et al, 2018). Poultryrequirements of zinc range from 30 to 40 μg / kg depending on a number of factors, including species or breeds, age,environmental conditions, diet composition, supplementation levels, and forms (Burrell et al, 2004;Rossiet al, 2007;Roy et al, 2013).…”
Section: Phagocytic Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…It is also indicated that Zn requirement for laying performance might not be su cient to maintain the hatchability and embryonic development of laying ducks. As reported previously, severe Zn de ciency in hen diets impaired egg production and embryonic development [29], whereas maternal Zn supplementation or in ovo injections of Zn in yolk can eliminate these adverse effects [30]. Therefore, it is necessary to assess Zn status measuring some speci c sensitive indicators to prevent the marginal Zn de ciency occurred in breeder diets.…”
Section: Discussionmentioning
confidence: 99%
“…However, ferrets and mice are more susceptible to zinc toxicity than other species such as the chick embryo 10 , 11 . The chick requires zinc for normal development and can tolerate high intake of zinc supplied in appropriate diet 12,13 . In uenza virus infection is lethal to the chick embryo.…”
Section: Introductionmentioning
confidence: 99%